Depression and race affect hospitalization costs of heart failure patients. Issue 2 (1st June 2015) - Husaini, Baqar A.; Levine, Robert S.; Novotny, Meggan L.; Cain, Van A.; Sampson, Uchechukwu K.A.; Moonis, Majaz
Abstract : Objective: Depression and anxiety are frequently observed in heart failure (HF) patients; however, the effect of such factors on hospitalization costs of HF patients, and whether such costs vary by race and gender remain poorly understood. This analysis delineated the prevalence of depression/anxiety among HF patients and estimated the effect of race and gender on hospitalization costs. Methods: We examined the 2008 files of the Tennessee Hospital Discharge Data System (HDDS) on patients (≥20 years of age) with a primary diagnosis of HF (ICD-9 codes 402, 404, and 428) along with demographic data, depression/anxiety diagnoses, hospital costs, and comorbidities. Among the HF sample ( n =16, 889) 53% were female and 23% were black. Race and gender differences in hospital costs were evaluated for the following three groups: (1) HF patients with depression/anxiety (HF +D ); (2) HF-only patients without depression/anxiety (HF O ); and (3) HF patients with other mental diagnoses (HF +M ). Results: HF was significantly ( p <0.000) higher among blacks compared to whites, and higher among males than females. Nearly 25% of HF patients had depression/anxiety (more whites and females were depressed). HF patients averaged more than 3 comorbidities (blacks had a greater number of comorbidities and hospitalization cost for the year). Costs were higher among HF +D patients compared to HF O patients. Among HF +D patients, costs were higher for black males compared with white males. These cost patterns prevailed largely because of higher comorbidities that required more re-admissions and longer hospital stays. Conclusion: Race and depression/anxiety are associated with increased hospitalization costs of HF patients. The higher costs among blacks reflect the higher burden of comorbidities, such as hypertension and diabetes, which calls for widespread dissemination, adoption, and implementation of proven interventions for the control of these comorbidities.